HUBUNGAN TES “TIMED UP AND GO” DENGAN FREKUENSI JATUH PADA LANSIA - Selamat Ginting; Siti Marlina (Jurnal Penelitian Keperawatan Medik, 2018)
Frequency falls in the elderly still a problem that often happens in Indonesiaespecially in the Village of Rumah Great Kec Biru-Biru Kabupaten Deli Serdang. High prevalence rates incident falls in the elderly, which makes researchers want to apply the TUG (Timed Up And Go) test through the amount of time provided and the ability of the elderly complete the test series with the time needed by the elderly themselves. This research aims to knowing Relationship of the TUG Test (Timed Up And Go) with Frequency of falls In the elderly in Rumah Great Kec Biru-Biru Kabupaten Deli Serdang. Where is this TUG test used for knowing balance and disruption of walking in the elderly. Data collection begins from March to June 2017 with a total of 64 respondent by using categorical analytic research and cross sectional approach as a sampling method. Research instrument used in the form of a demographic data questionnaire, a TUG (Timed Up And Go) test questionnaire and a Meter Meter. The results showed that the sign value was 0.002 <p-value (0.05) indicating meaningful correlation between TUG Test scores (Timed Up and Go) with Falling Frequency In the elderly. This research is expected can be useful next time in doing the TUG test with the Frequency of Falling in the Elderly